Elevated homocysteine is associated with increased rates of epigenetic aging in a population with mild cognitive impairment - Holmes, HE; Valentin, RE; Jernerén, F; de Jager Loots, CA; Refsum, H; Smith, AD; Guarente, L; Dellinger, RW; Sampson, D; Alzheimer's Disease Neuroimaging Initiative (Wiley Open Access, 2024)
Elevated plasma total homocysteine (tHcy) is associated with the development of Alzheimer's disease and other forms of dementia. In this study, we report the relationship between tHcy and epigenetic age in older adults with mild cognitive impairment from the VITACOG study. Epigenetic age and rate of aging (ROA) were assessed using various epigenetic clocks, including those developed by Horvath and Hannum, DNAmPhenoAge, and with a focus on Index, a new principal component‐based epigenetic clock that, like DNAmPhenoAge, is trained to predict an individual's “PhenoAge.” We identified significant associations between tHcy levels and ROA, suggesting that hyperhomocysteinemic individuals were aging at a faster rate. Moreover, Index revealed a normalization of accelerated epigenetic aging in these individuals following treatment with tHcy‐lowering B‐vitamins. Our results indicate that elevated tHcy is a risk factor for accelerated epigenetic aging, and this can be ameliorated with B‐vitamins. These findings have broad relevance for the sizable proportion of the worldwide population with elevated tHcy.